KAJIAN PELAN INDUK SALIRAN MESRA ALAM SERIAN, SARAWAK - Zayn Al-Abideen, Gregory; Bambang, Karsono (Department of Irrigation and Drains Malaysia, 2021)
A Stormwater Management and Drainage Master Plan Study for Serian, Sarawak which can be used as a reference for future urban drainage planning in development or re-development works.